BLOCKADE OF EPIDERMAL GROWTH FACTOR RECEPTOR, CYCLOXYGENASE-2 (COX-2) AND MAMMALIAN TARGET OF RAPAMYCIN (M-TOR) IN ANIMAL MODEL OF LUNG CANCER (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
To explore the effectiveness and possible toxicity of the use of epidermal growth factor receptor inhibitor (EGFR Inhibitor), Celecoxib (COX2 inhibitor) and Sirolimus (m-TOR inhibitor) as single agents and drug combinations for the treatment of lung cancer in an experimental model. Lung cancer was induced in Balb-C mice by intraperitoneal injection urethane. Mice were treated with water (control) , Erlotinib (E) (50 mg/kg), Celecoxib (X) (50 mg/kg), Sirolimus (R) (2 mg/kg) given alone and in the following doublet and triplet combinations in the same dosages for 7 days. The number of pulmonary nodules in the combined treatment was significantly inhibited compared with control (p=0.010); E (p=0.028), EX (p=0.010), ERX (p=0.040) showed a smaller number of statistically significant nodules. Regarding coat changes we observe statistically significant differences among groups (p<0.001) where ERX and ER had a higher occurrence of this change. There was a higher incidence of skin rashes in groups: E (p<0.001), ER (p<0.0001), and ERX (p<0.001). Regarding weight we identify weight loss in the ERX (p=0.025). The combination of EGFR inhibitor, COX-2 inhibitor and m-TOR inhibitor had anti-tumor activity in experimental lung cancer. The combination of Celecoxib treatment with Erlotinib is a suggestion for decrease of dermatological events in patients. The combination of EGFR inhibitor and Sirolimus does not decrease the number of lung nodules and potentiates adverse events.